Lnc2300 is a cis‐acting long noncoding RNA of CYP11A1 in ovarian granulosa cells. Issue 11 (8th September 2022) - Wang, Miaomiao; Wang, Yang; Yao, Wang; Du, Xing; Li, Qifa
Abstract: The high level of progesterone and 17β‐estradiol ratio (P4/E2) in follicular fluid has been considered as a biomarker of follicular atresia. CYP11A1, the crucial gene encoding the rate‐limiting enzyme for steroid hormone synthesis, has been reported differently expressed in the ovary during follicular atresia. However, the regulation mechanism of CYP11A1 expression during follicular atresia still remains unclear. Here, we have demonstrated that lnc2300, a novel pig ovary‐specific highly expressed cis‐ acting long noncoding RNA (lncRNA) transcribed from chromosome 7, has the ability to induce the expression of CYP11A1 and inhibit the apoptosis of porcine granulosa cells (GCs). Mechanistically, lnc2300, mainly located in the cytoplasm of porcine GCs, sponges and suppresses the expression of miR‐365‐3p through acting as a competing endogenous RNA (ceRNA), which further relieves the inhibitory effects of miR‐365‐3p on the expression of CYP11A1 . Besides, CYP11A1 is validated as a direct functional target of miR‐365‐3p in porcine GCs. Functionally, lnc2300 is an antiapoptotic lncRNA that reduces porcine GC apoptosis by inhibiting the proapoptotic function of miR‐365‐3p. In summary, our findings reveal a cis ‐acting regulation mechanism of CYP11A1 through lncRNA, and define a novel signaling pathway, lnc2300/miR‐365‐3p/CYP11A1 axis, which is involved in the regulation of GC apoptosis and follicular atresia.